The academic an non-academic factors related to students subject failing at the Psychology Departament of the University of El Salvador, semester I-2000 - Amaya Coreas, María Cristina (2024)
The present report contains analysis of the data collected through a survey among students from the Psychology Department. The age of the students varies from nineteen to thirty nine year-old, among 34 female students and 14 male students. The questionnaires were answered during a week and a half. The major problem was to be able to reach students through, when they were found they were very collaborative who helped the researchers out to find the other students that became part of the sample. It was just a matter of looking for them that took most of the time because once they were contacted they helped out.